ANALYSIS EFFECT OF CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE WITH VARIABLE CONTROL FIRM SIZE - Yanti Damai; yulinda yulinda (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2019)
This study is aimed to examine the effect of corporate governance on financial performance with variable control firm size. Corporate governance is measured using board of commissioners, proportion of outside commissioners, board of directors, institutional ownership, managerial ownership, and audit committee. Financial performance is measured using tobins q. This study used variable control which is firm size where as measured used log natural assets. This study used sample were as public listed companies in Indonesian Stock Exchange (IDX) in period 2011-2015. Thus, this sampling method used purposive sampling technique. The result of this study showed that board of commissioners, board of directors, institutional ownership, managerial ownership, audit commitee not influence to financial performance. This study is showed proportion of outside commissioners influence to financial performance. The purpose study determine where is to add more independent variable. In addition, financial performance is measured used EVA (Economic Value Added) and expanding the corporate companies. More over the result in this study is have implications to each hypothesis.